Feasibility of the flipped classroom approach for health education in a clinical weight loss program - Kameron Suire; Mary Hastert; Stephen D. Herrmann; Joseph E. Donnelly (Elsevier, 2024)
Aim: To assess the feasibility of the flipped classroom pedagogy in a clinical weight loss program and its impact on 6-month weight change. Methods: Adults with overweight/obesity enrolled in a 6-month program with a structured diet (portion-controlled meals and fruits/vegetables) and exercise plan (≥150mins/week), plus weekly, 1-h group education sessions. Sessions used a flipped classroom approach: educational content was delivered beforehand via podcast/video and book readings and session time involved application-based activities (e.g., case studies, games). Satisfaction surveys were completed at 3 months. Weight change was assessed using paired t-tests (SAS 9.4, significance 0.05). Results: Eighteen participants completed 6 months (retention 94%). Participants maintained diet adherence and exercise at 3 months (∼84% diet adherence, ∼153mins exercise/week) and 6 months (∼83% diet adherence, ∼158mins exercise/week), as well as attendance to behavioral sessions (3 months: 77%; 6mo: 71%). Satisfaction surveys showed high program enjoyment (∼8.1/10). Mean weight change at 3 and 6 months was −6.5 ± 4.2% and − 9.3 ± 5.0% (both p < 0.01), respectively. Conclusion: The flipped classroom pedagogy was feasible for delivery in a clinical weight loss program and supported significant 6-month weight loss. Innovation: This is the first evaluation of the flipped classroom in a clinical setting and supports the investigation of this pedagogy in weight management.